2016
DOI: 10.3389/fpsyg.2015.02023
|View full text |Cite
|
Sign up to set email alerts
|

Music Makes the World Go Round: The Impact of Musical Training on Non-musical Cognitive Functions—A Review

Abstract: Musical training is becoming increasingly popular as a topic for scientific research. Here we review the available studies investigating whether and to which degree musical experience generalizes to cognitive functions unrelated to music abilities in healthy humans. In general, it seems that musical training is associated with enhancing effects, even if sometimes only restricted to the auditory domain, on various cognitive functions spanning from executive control to creativity. We conclude that musical engage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 56 publications
1
88
0
6
Order By: Relevance
“…These outcomes suggest that there may be an overlap between brain networks involved in musical rhythm and cognitive control and provide a basis for further investigation of the potential for rhythm-based training to strengthen cognitive function. Although correlational studies cannot establish a causal relationship between music training and inhibitory control, converging evidence has demonstrated enhanced cognitive and perceptual function in musicians (see Benz, Sellaro, Hommel, & Colzato, 2015, for a recent review). Percussionists outperformed nonpercussionists in all of our measures of interest; however, our regression analyses suggest the results are not solely driven by group differences, because drumming consistency and the neural index of beat alignment each explain unique variance in inhibitory control, above and beyond group membership and demographic factors (age, sex, and IQ).…”
Section: Discussionmentioning
confidence: 99%
“…These outcomes suggest that there may be an overlap between brain networks involved in musical rhythm and cognitive control and provide a basis for further investigation of the potential for rhythm-based training to strengthen cognitive function. Although correlational studies cannot establish a causal relationship between music training and inhibitory control, converging evidence has demonstrated enhanced cognitive and perceptual function in musicians (see Benz, Sellaro, Hommel, & Colzato, 2015, for a recent review). Percussionists outperformed nonpercussionists in all of our measures of interest; however, our regression analyses suggest the results are not solely driven by group differences, because drumming consistency and the neural index of beat alignment each explain unique variance in inhibitory control, above and beyond group membership and demographic factors (age, sex, and IQ).…”
Section: Discussionmentioning
confidence: 99%
“…These domains include general cognitive benefits (including language benefits as a major sub-field), auditory processing benefits, motor control benefits, social benefits, and health benefits. The general cognitive benefits mentioned as arising from musical engagement are: general reasoning skills (Miendlarzewska and Trost 2014); academic achievement (Dawson 2011); intelligence (Benz et al 2016;Levitin 2013); cognitive ability (Kraus and Chandrasekaran 2010); numeracy and spatial cognition (Levitin 2013); cognitive control (Dawson 2011), processing speed (Benz et al 2016); temporal processing skills (Miendlarzewska and Trost 2014); verbal memory (Benz et al 2016;Dawson 2011;Levitin 2013); working memory performance (Kraus and Chandrasekaran 2010); executive control over attention (Putkinen et al 2015); and visual attention (Benz et al 2016). It is also suggested that life-long musical training may delay or reverse age-related cognitive decline (Benz et al 2016).…”
Section: Review Papersmentioning
confidence: 99%
“…The suggested benefits of musical engagement for linguistic development include: improved language processing and language-learning ability (Dawson 2011); improved vocabulary, greater reading ability, and stronger neural activation to pitch patterns in native language (Kraus and Chandrasekaran 2010); more accurate brainstem encoding of linguistic pitch patterns in an unfamiliar tonal language (Kraus and Slater 2015); improved phonological awareness and spelling performance in dyslexic children, and better speech segmentation (François et al 2013); and improved phonemic awareness (Benz et al 2016).…”
Section: Review Papersmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard general cognitive processes (attention, working memory, and executive functions), there are plenty of positive findings of music training to enhance these higher-order functions as well (Benz et al 2016). However, these effects are quite sensitive to the testing paradigms and thus more research on this domain is needed (see critical review by Jaschke, Eggermont, Honing, & Scherder, 2013).…”
mentioning
confidence: 99%